The Influence of Influencer Marketing and Lifestyle on Purchase Decisions of Virtual Game Product Mobile Legends: Bang Bang - Elsa Nabella; Supriyono; Wilma Cordelia Izaak (Jurnal Ekonomi dan Bisnis Digital, 2023)
Understanding the impact of Influencer Marketing and Lifestyle on the Purchase Decisions of the online virtual game Mobile Legends: Bang Bang is the primary objective of this research. The population under research consists of Mobile Legends players who are students in Surabaya and have purchased a skin hero in the game Mobile Legends: Bang Bang and used it during gameplay. This research utilized a non-probability sampling method with a purposive sampling technique. The sample size for this research was 110 respondents. Data for this research was collected through questionnaire responses from the respondents as well as from various sources such as books, articles, and journals. The analytical tool employed in this research was Partial Least Squares (PLS). The findings of the research indicated that both Influencer Marketing and Lifestyle had a significant impact on the Purchase Decision for Mobile Legends: Bang Bang.